Plasma Ghrelin Levels Are Associated with Anorexia but Not Cachexia in Patients with NSCLC - Blauwhoff-Buskermolen, Susanne; Langius, Jacqueline A. E.; Heijboer, Annemieke C.; Becker, Annemarie; de van der Schueren, Marian A. E.; Verheul, Henk M. W. (Frontiers in Physiology, 2017)
Background & Aims: The ghrelin receptor is one of the new therapeutic targets in the cancer anorexia-cachexia syndrome. Previous studies revealed that plasma ghrelin levels were high in patients with anorexia nervosa and low in obese subjects. We studied to what extent ghrelin levels are related with anorexia and cachexia in patients with cancer. Materials and methods: Fasted ghrelin levels were determined as well as anorexia and cachexia in patients with stage III/IV non-small cell lung cancer before chemotherapy. Total plasma ghrelin was measured by radioimmunoassay. Anorexia was measured with the FAACT-A/CS questionnaire (cut-off value ≤37). Cachexia was determined as >5% weight loss (WL) in 6 months or >2% WL in 6 months in combination with low BMI or low muscle mass. The Kruskal-Wallis test was performed to assess differences in plasma ghrelin levels between four groups: patients with (+) or without (-) anorexia (A) or cachexia (C). Multiple regression analyses were performed to assess differences in plasma ghrelin levels between patients C+ and C- and patients with A+ and A- (adjusted for age and sex). Results: Forty patients with stage III (33%) or stage IV (68%) were recruited, of which 50% was male. Mean age was 59.6±10.3 years. Sixteen patients had no anorexia or cachexia (A-C-), seven patients had both anorexia and cachexia (A+C+), ten patients had anorexia without cachexia (A+C-) and seven patients had cachexia without anorexia (A-C+). The levels of total plasma ghrelin were significantly different between the four groups of patients with or without anorexia or cachexia (p=0.032): the A+C- patients had significantly higher ghrelin levels (median (IQR): 1754(1404-2142) compared to the A-C+ patients (1026(952-1357), p=0.003). A+ patients had significantly higher ghrelin levels compared A- patients (C+ and C- combined, β: 304 , p=0.020). Plasma ghrelin levels were not significantly different in C+ patients compared to C- patients (A+ and A- combined, β: -99, p=0.450). Conclusions: Patients with anorexia had significantly higher ghrelin levels compared to patients without anorexia. We therefore hypothesize that patients with cancer anorexia might benefit from treatment with a ghrelin receptor agonist to prevent WL and deterioration in physical functioning.